Dissecting the Role of Curcumin in Tumour Growth and Angiogenesis in Mouse Model of Human Breast Cancer - Bimonte, Sabrina (Biomed Res Int, 2015)
Breast cancer is considered the most common cancer for women worldwide and it is now the second leading cause of cancer-related deaths among females in the world. Since breast cancer is highly resistant to chemotherapy, alternative anticancer strategies have been developed. In particular, many studies have demonstrated that curcumin, a derivative of turmeric, can be used as natural agent in treatment of some types of cancer by playing antiproliferative and antioxidant effects. In our study, we assessed the antitumor activities of curcumin in ER-negative human breast cancer cell line resistant to chemotherapy, MDA.MB231 by in vitro and in vivo experiments. In vitro data allowed us to demonstrate that curcumin played a role in regulation of proliferation and apoptosis in MDA.MB231 cells. In vivo, by generation of mouse model of breast cancer, we showed that treatment of curcumin inhibited tumor growth and angiogenesis. Specifically, we showed that curcumin is able to deregulate the expression of cyclin D1, PECAM-1, and p65, which are regulated by NF-κB. Our data demonstrated that curcumin could be used as an adjuvant agent to chemotherapy in treatment of triple negative breast cancer.